Employee reactions of post-acquisition integration in cross-border acquisitions - Luomansuu, Sanni (My University, 2015)
Mergers and acquisitions have long been a common strategic instrument for companies’ continuous growth and constant corporate renewal. Globalization of business has increased the amount of acquisition across national borders. Recent studies suggest that even though the popularity of cross-border M&A’s is increasing, they are not highly successful. There are substantial amount of research that examines the strategic and financial aspects of M&A, but the high percentage of failures has shifted the focus to human side of acquisition to understand the behavioural effects of M&A on employees. The purpose of this study is to contribute to the understanding of employee reactions in cross-border acquisitions by exploring employee behaviour in post-acquisition integration, and building and testing a typology of employee reactions. The theoretical framework of the study is created based on existent typology of employee behaviour during acquisitions developed by Bourantas and Nikandrou (1998). The data of the study was collected in May 2014 using online questionnaire. The data source was a single cross-border acquisition. The data was analyzed with quantitative research methods including correlation analysis, t-test, standard scores, contingency tables and chi-square tests. The result of the study indicates that acquisition process, especially post-acquisition integration phase, has a great effect on employees at all levels. Most of the previous studies focus on employees in the acquired company but according to the results of this study integration period affects also employees in the acquiring company. In the case acquisition, the employees of the acquiring company were more resistive in their behaviour compared to the employees in the acquired company. Thus, great attention should be paid on all employees affected by the integration.
Keywords: cross-border acquisitions; employee reactions; behavioural response typology; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|